Biomass hard carbon sodium ion battery negative electrode material with high platform capacity and preparation method of biomass hard carbon sodium ion battery negative electrode material

By using alkaline solution treatment and activator activation technology in biomass hard carbon materials, a rich microporous structure is formed, which solves the problem of limited platform capacity of existing hard carbon materials, and achieves the effect of high platform capacity and high first-week efficiency.

CN119706841AActive Publication Date: 2025-03-28SHENZHEN JANAENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411956697.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-03-28
Estimated Expiration
2044-12-29

AI Technical Summary

Technical Problem

The existing hard carbon materials have limited platform capacity in sodium ion batteries, and it is difficult for activators to penetrate deep into the material, resulting in uneven pore structure and affecting battery performance.

Method used

By performing alkaline solution treatment on biomass raw materials, the network structure of the material is broken, so that the activator can penetrate deep into the inside, and then a rich microporous structure is formed during the low-temperature carbonization and high-temperature carbonization, thereby enhancing the platform capacity of the material.

Benefits of technology

The platform capacity of the negative electrode material of sodium ion battery has been significantly improved, the charging and discharging efficiency in the first week has been improved, and the process cost has been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706841A_ABST
    Figure CN119706841A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass hard carbon sodium ion battery negative electrode material with high platform capacity and a preparation method thereof. The preparation method comprises the following steps: S1, pretreating raw materials to obtain a primary raw material; s2, alkaline solution treatment: carrying out temperature control treatment under the condition of an alkaline solution to obtain a biomass raw material treated by the alkaline solution; s3, lignin removal treatment: performing centrifugation, acid pickling, water washing and drying to obtain a biomass raw material of which part of lignin is removed; s4, activating agent treatment: carrying out temperature control reaction in an activating agent solution, and then centrifuging and drying to obtain a biomass raw material rich in an activating agent; s5, carbonization and activation: carrying out carbonization and activation to obtain an activated material; s6, post-treatment: carrying out acid washing and water washing to be neutral, and drying to obtain a low-temperature carbonized material rich in a microporous structure; and S7, high-temperature carbonization: performing high-temperature carbonization to obtain the sodium-ion battery hard carbon negative electrode material rich in micropores. The method has the characteristics that the platform capacity is effectively improved, the first-cycle charging and discharging efficiency is high, and the process cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a biomass hard carbon sodium ion battery negative electrode material with a high platform capacity and a preparation method thereof. Background Art

[0002] With the rapid development of smart grids and electric vehicles, limited lithium resources can no longer meet social needs. Therefore, sodium-ion batteries, which are cheap and have abundant raw material reserves, have become an excellent alternative.

[0003] Hard carbon is currently the most promising anode material for sodium-ion batteries, but its low platform capacity limits the improvement of the energy density of sodium-ion batteries. Due to the complex structure of hard carbon materials and the controversial sodium storage mechanism, it is more challenging to develop anode materials for sodium-ion batteries with high platform capacity.

[0004] At present, the industry widely uses hard templates as activators, such as ZnCl2, MgCl2, etc. This type of activator is less corrosive and has the advantages of low equipment consumption and mild process conditions. However, it also has its defects: for example, it is difficult for the activator to enter the interior of the material, and it is easy to stay and accumulate on the surface of the material. The oxides formed during calcination will accumulate on the surface of the material, thereby forming macropores and mesopores, resulting in a large specific surface area and low micropore content of the hard carbon material, resulting in limited capacity improvement of the hard carbon negative electrode material and low first efficiency. Summary of the invention

[0005] The purpose of the present invention is to provide a biomass hard carbon sodium ion battery negative electrode material with a high platform capacity and a preparation method thereof, which has the characteristics of effectively improving the platform capacity, high first-week charge and discharge efficiency and low process cost.

[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity, comprising the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials; S2, alkaline solution treatment: the preliminary raw material obtained in step S1 is treated under alkaline solution conditions under temperature control to obtain a biomass raw material treated with alkaline solution; S3, lignin removal treatment: centrifuging the biomass raw material treated with the alkaline solution in step S2, then acid-washing and water-washing to neutrality, and finally drying to obtain a biomass raw material with some lignin removed; S4, activator treatment: the biomass raw material from which part of the lignin has been removed obtained in step S3 is subjected to temperature-controlled reaction in an activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator; S5, carbonization and activation: carbonizing and activating the biomass raw material rich in activating agent obtained in step S4 to obtain an activated material; S6, post-processing: pickling and washing the activated material obtained in step S5 to neutrality, and drying to obtain a low-temperature carbonized material rich in microporous structure; S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores.

[0007] In step S2, the role of the alkaline solution is to dissolve part of the lignin, break the dense network structure of the biomass raw material, and enable the activator used in the subsequent steps to fully penetrate into the biomass raw material. The structure of biomass materials is very complex and diverse. From a microscopic level, it is mainly composed of lignin, cellulose and hemicellulose. Lignin, cellulose and hemicellulose are often connected to each other to form a lignin-carbohydrate complex. Among them, lignin is a polyphenol polymer with a three-dimensional network structure formed by the interconnection and irregular coupling of phenylpropane structural units through carbon-carbon bonds (C-C) and ether bonds (-0-). Lignin runs through cellulose and hemicellulose, plays a role in connecting the two, and then forms a very strong network structure. In order to allow the activator to enter the interior of the material, the dissolution of lignin by the alkaline solution is used to break the tight network structure between cellulose, hemicellulose and lignin without destroying the structure of the material itself, creating a path for the activator to penetrate into the biomass raw material.

[0008] In step S4, the purpose of adding the activator is to calcine the activator to form oxides in the subsequent low-temperature carbonization stage. After the generated oxides are removed by pickling, a pore structure is formed at the position where the oxides are missing. In order to make the formed pore structure a microporous structure, the mass fraction of inorganic salts or organic salts containing zinc, magnesium and calcium needs to be controlled at 5% to 20%, so that the activator can enter the material uniformly in sufficient quantity, and the problem of activator enrichment will not occur, thereby generating distributed and dispersed oxides in the material, so that the material has a rich microporous structure.

[0009] Further, in step S2, the alkaline solution is one or more of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution, potassium hydroxide solution, potassium carbonate solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 2-10 mol / L; the conditions for the temperature control reaction are: temperature 60-120°C, time 2-10h. Specifically, if the concentration of the alkaline solution is too low, that is, too little lignin is dissolved, the tight network structure connected by lignin cannot be broken, which directly affects the penetration of the activator into the material, resulting in poor activation effect; if the concentration of the alkaline solution is too high, that is, the lignin is completely dissolved, it will cause the structure of the material to collapse, and then cause the interlayer spacing to be greatly reduced, affecting the insertion and extraction of sodium ions, and ultimately causing a significant decrease in battery performance.

[0010] Further, in step S4, the activator is one or more of zinc chloride, magnesium chloride, calcium chloride, zinc nitrate, magnesium nitrate, zinc acetate, magnesium acetate, calcium acetate, zinc gluconate, magnesium gluconate, calcium gluconate, zinc citrate, magnesium citrate, and calcium citrate, and the amount of the activator added is 5-20 wt.% of the amount of biomass raw material added, and the temperature control reaction conditions are: temperature 50-80°C, time 5-20h. Specifically, if the amount of the activator added is too high, it is easy for the activator to be enriched inside the material, resulting in too much or too large oxides formed at the same site, resulting in macropores and mesoporous structures, and reducing the performance of the battery; if the amount of the activator added is too low, less activator enters the material, less oxides are generated, and fewer pore structures are formed, which does not significantly improve the capacity.

[0011] Further, in step S5, the carbonization activation conditions are: heating rate 2-10 ° C / min, temperature 300-600 ° C, treatment time 2-5 h; protective gas is nitrogen and / or argon. Specifically, the carbonization activation temperature affects the effect of the present invention: if the carbonization activation temperature is too low, the activator cannot be completely converted into metal oxides, resulting in the inability to completely remove the activator in the subsequent pickling step; if the carbonization activation temperature is too high, the carbon material has a high degree of carbonization, resulting in pore collapse and closure, which is also not conducive to the removal of the activator in the subsequent pickling step.

[0012] Further, in step S7, the conditions for high-temperature carbonization are: heating rate 0.5-5 ℃ / min, carbonization temperature 1200-1600 ℃, and carbonization time 2-10 h. Specifically, the high-temperature carbonization temperature needs to be between 1200 and 1600 ℃. The purpose is that during the high-temperature carbonization stage, the original microporous structure of the low-temperature carbonized material is closed at high temperature to form a closed-pore structure. Such a structure can store sodium and increase capacity, and at the same time, it will also make the material have a smaller specific surface area, thereby not affecting the first-cycle efficiency of the hard carbon negative electrode material. If the high-temperature carbonization temperature is too low, the microporous structure in the low-temperature carbonized material cannot be completely closed, resulting in a larger specific surface area of ​​the material, affecting the first-cycle efficiency of the material; if the high-temperature carbonization temperature is too high, the degree of graphitization of the carbon material will be higher, and the interlayer spacing will be smaller, which is not conducive to the embedding and extraction of sodium ions, and will have a negative impact on the performance of the material.

[0013] Furthermore, in steps S3 and S6, the pickling solution is one or more of hydrochloric acid, nitric acid solution, hydrofluoric acid, formic acid, acetic acid, and phytic acid with a mass fraction of 2-10%.

[0014] Furthermore, in step S4, the concentration of the filtered activator filtrate is calibrated and then added to the required concentration, and the filtrate can be recycled to increase economic benefits.

[0015] Furthermore, in step S1, the biomass raw material is one or more of walnut shells, coconut shells, apricot shells, coffee shells, peanut shells, fruit peels, reeds, wood chips, bamboo chips, sunflower stalks, corn stalks, wheat stalks, and starch.

[0016] Another aspect of the present invention is to protect a biomass hard carbon sodium ion battery negative electrode material, which is prepared by the above-mentioned preparation method.

[0017] The present invention discloses a biomass hard carbon sodium ion battery negative electrode material with high platform capacity and a preparation method thereof, which has the following beneficial effects: First, the platform capacity is effectively improved. In the present invention, through alkaline dissolution combined with hard template activation pore formation, a rich microporous structure is formed inside the biomass material, which greatly improves the low-potential platform capacity of the hard carbon negative electrode material; Second, the first cycle charge and discharge efficiency is high. The preparation method of the present invention produces a large number of micropores, non-macropores and mesopores in the material. The micropore structure is easy to close after high-temperature carbonization, so that the material has the characteristics of small specific surface area. Hard carbon materials with small specific surface area have higher first cycle efficiency and processability. Third, the process cost is low. The preparation method of the present invention can allow the activator to enter the interior of the biomass material to exert its effect, reduce the amount of activator used, greatly increase the use efficiency of the activator, and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the charge and discharge curve of the first week of application example 1; Figure 2 This is the charge and discharge curve of the first week of application example 2; Figure 3 This is the first week charge and discharge curve of Comparative Example 1; Figure 4 This is the first week charge and discharge curve of Comparative Example 2;. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0020] The present invention discloses a method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity, comprising the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials; S2, alkaline solution treatment: the preliminary raw material obtained in step S1 is treated under alkaline solution conditions under temperature control to obtain a biomass raw material treated with alkaline solution; S3, lignin removal treatment: centrifuging the biomass raw material treated with the alkaline solution in step S2, then acid-washing and water-washing to neutrality, and finally drying to obtain a biomass raw material with some lignin removed; S4, activator treatment: the biomass raw material from which part of the lignin has been removed obtained in step S3 is subjected to temperature-controlled reaction in an activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator; S5, carbonization and activation: carbonizing and activating the biomass raw material rich in activating agent obtained in step S4 to obtain an activated material; S6, post-processing: pickling and washing the activated material obtained in step S5 to neutrality, and drying to obtain a low-temperature carbonized material rich in microporous structure; S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores.

[0021] Further, in step S2, the alkaline solution is one or more of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution, potassium hydroxide solution, potassium carbonate solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 2-10 mol / L; the temperature control reaction conditions are: temperature 60-120°C, time 2-10h.

[0022] Furthermore, in step S4, the activator is one or more of zinc chloride, magnesium chloride, calcium chloride, zinc nitrate, magnesium nitrate, zinc acetate, magnesium acetate, calcium acetate, zinc gluconate, magnesium gluconate, calcium gluconate, zinc citrate, magnesium citrate, and calcium citrate, and the amount of the activator added is 5-20 wt.% of the amount of biomass raw material added, and the temperature control reaction conditions are: temperature 50-80°C, time 5-20h.

[0023] Furthermore, in step S5, the carbonization activation conditions are: heating rate 2-10°C / min, temperature 300-600°C, treatment time 2-5 h; and protective gas is nitrogen and / or argon.

[0024] Furthermore, in step S7, the conditions for high temperature carbonization are: heating rate 0.5-5°C / min, carbonization temperature 1200-1600°C, and carbonization time 2-10 h.

[0025] Furthermore, in steps S3 and S6, the pickling solution is one or more of hydrochloric acid, nitric acid solution, hydrofluoric acid, formic acid, acetic acid, and phytic acid with a mass fraction of 2-10%.

[0026] Furthermore, in step S4, the concentration of the filtered activator filtrate is calibrated and then added to a desired concentration.

[0027] Furthermore, in step S1, the biomass raw material is one or more of walnut shells, coconut shells, apricot shells, coffee shells, peanut shells, fruit peels, reeds, wood chips, bamboo chips, sunflower stalks, corn stalks, wheat stalks, and starch.

[0028] Another aspect of the present invention is to protect a biomass hard carbon sodium ion battery negative electrode material, which is prepared by the above-mentioned preparation method.

[0029] Example 1 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with high platform capacity, and its preparation method comprises the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials. Specifically, the biomass raw materials are walnut shells, coconut shells, and apricot shells.

[0030] S2. Alkaline solution treatment: The preliminary raw material obtained in step S1 is treated with alkaline solution under temperature control to obtain a biomass raw material treated with alkaline solution. Specifically, the alkaline solution is a sodium hydroxide solution, and the concentration of the alkaline solution is 10 mol / L; the temperature control reaction conditions are: temperature 90°C, time 2h.

[0031] S3, lignin removal treatment: centrifuge the biomass raw material treated with the alkaline solution in step S2, then acid wash and water wash to neutrality, and finally dry to obtain a biomass raw material with some lignin removed. Specifically, the acid washing solution is hydrochloric acid with a mass fraction of 10%.

[0032] S4, activator treatment: the biomass raw material with some lignin removed obtained in step S3 is subjected to temperature-controlled reaction in the activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator. Specifically, the filtered activator filtrate is calibrated and then added to the required concentration, the activator is zinc chloride and magnesium chloride, the amount of activator added is 20 wt.% of the amount of biomass raw material added, and the temperature-controlled reaction conditions are: temperature 65°C, time 5h.

[0033] S5, carbonization activation: the biomass raw material rich in activator obtained in step S4 is carbonized and activated to obtain an activated material. Specifically, the carbonization activation conditions are: heating rate 10 °C / min, temperature 450 °C, treatment time 2 h; protective gas is nitrogen and argon.

[0034] S6, post-treatment: pickling and water washing the activated material obtained in step S5 until it is neutral, and drying to obtain a low-temperature carbonized material rich in microporous structure. Specifically, the pickling solution is hydrochloric acid with a mass fraction of 10%.

[0035] S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores. Specifically, the conditions for high temperature carbonization are: heating rate 5 °C / min, carbonization temperature 1400 °C, and carbonization time 2h.

[0036] Example 2 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with high platform capacity, and its preparation method comprises the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials. Specifically, the biomass raw materials are walnut shells, coconut shells, wheat straw, and starch.

[0037] S2. Alkaline solution treatment: The preliminary raw material obtained in step S1 is treated with alkaline solution under temperature control to obtain a biomass raw material treated with alkaline solution. Specifically, the alkaline solution is potassium carbonate solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 6 mol / L; the temperature control reaction conditions are: temperature 60°C, time 10h.

[0038] S3, lignin removal treatment: centrifuge the biomass raw material treated with the alkaline solution in step S2, then acid wash and water wash to neutrality, and finally dry to obtain a biomass raw material with some lignin removed. Specifically, the acid washing solution is acetic acid and phytic acid with a mass fraction of 5%.

[0039] S4, activator treatment: the biomass raw material with some lignin removed obtained in step S3 is subjected to temperature-controlled reaction in an activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator. Specifically, the filtered activator filtrate is calibrated and then added to the required concentration, the activator is zinc citrate, magnesium citrate, and calcium citrate, the amount of activator added is 12 wt.% of the biomass raw material, and the temperature-controlled reaction conditions are: temperature 50°C, time 20h.

[0040] S5, carbonization activation: the biomass raw material rich in activator obtained in step S4 is carbonized and activated to obtain an activated material. Specifically, the carbonization activation conditions are: heating rate 6 °C / min, temperature 300 °C, treatment time 5 h; protective gas is nitrogen.

[0041] S6, post-treatment: pickling and water washing the activated material obtained in step S5 until it is neutral, and drying to obtain a low-temperature carbonized material rich in microporous structure. Specifically, the pickling solution is a nitric acid solution with a mass fraction of 6%.

[0042] S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores. Specifically, the conditions for high temperature carbonization are: heating rate 3 °C / min, carbonization temperature 1200 °C, and carbonization time 10 h.

[0043] Example 3 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with high platform capacity, and its preparation method comprises the following steps: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials. Specifically, the biomass raw materials are corn straw, wheat straw, and starch.

[0044] S2. Alkaline solution treatment: The preliminary raw material obtained in step S1 is treated with alkaline solution under temperature control to obtain a biomass raw material treated with alkaline solution. Specifically, the alkaline solution is sodium hydroxide solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 2 mol / L; the temperature control reaction conditions are: temperature 120°C, time 6 hours.

[0045] S3, lignin removal treatment: centrifuge the biomass raw material treated with the alkaline solution in step S2, then acid wash and water wash to neutrality, and finally dry to obtain a biomass raw material with some lignin removed. Specifically, the acid washing solution is formic acid, acetic acid, and phytic acid with a mass fraction of 2%.

[0046] S4, activator treatment: the biomass raw material with part of the lignin removed obtained in step S3 is subjected to temperature control reaction in the activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator. Specifically, the filtered activator filtrate is calibrated and then added to the required concentration, the activator is calcium acetate, zinc gluconate, magnesium gluconate, and calcium citrate, the amount of activator added is 5 wt.% of the amount of biomass raw material added, and the temperature control reaction conditions are: temperature 80°C, time 12h.

[0047] S5, carbonization activation: the biomass raw material rich in activator obtained in step S4 is carbonized and activated to obtain an activated material. Specifically, the carbonization activation conditions are: heating rate 2 °C / min, temperature 600 °C, treatment time 2-5 h; protective gas is argon.

[0048] S6, post-treatment: pickling and water washing the activated material obtained in step S5 until it is neutral, and drying to obtain a low-temperature carbonized material rich in microporous structure. Specifically, the pickling solution is 2% by mass of hydrochloric acid, formic acid, and acetic acid.

[0049] S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores. Specifically, the conditions for high temperature carbonization are: heating rate 0.5 °C / min, carbonization temperature 1600 °C, and carbonization time 6 h.

[0050] Example 4 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with high platform capacity, and its preparation method comprises the following steps: S1. Raw material pretreatment: crush and sieve the biomass raw materials to obtain preliminary raw materials. Specifically, the biomass raw materials are walnut shells, coconut shells, apricot shells, coffee shells, peanut shells, and starch.

[0051] S2. Alkaline solution treatment: The preliminary raw material obtained in step S1 is treated with alkaline solution under temperature control to obtain a biomass raw material treated with alkaline solution. Specifically, the alkaline solution is sodium bicarbonate solution, potassium hydroxide solution, potassium carbonate solution, and barium hydroxide solution, and the concentration of the alkaline solution is 4 mol / L; the temperature control reaction conditions are: temperature 80°C and time 8h.

[0052] S3, lignin removal treatment: centrifuge the biomass raw material treated with the alkaline solution in step S2, then acid wash and water wash to neutrality, and finally dry to obtain a biomass raw material with some lignin removed. Specifically, the acid washing solution is 4% by mass of hydrochloric acid, formic acid, and acetic acid.

[0053] S4, activator treatment: the biomass raw material with some lignin removed obtained in step S3 is subjected to temperature-controlled reaction in an activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator. Specifically, the filtered activator filtrate is calibrated and then added to the required concentration, the activator is calcium acetate, zinc gluconate, magnesium gluconate, and calcium citrate, the amount of activator added is 10 wt.% of the amount of biomass raw material added, and the temperature-controlled reaction conditions are: temperature 70°C, time 12h.

[0054] S5, carbonization activation: the biomass raw material rich in activator obtained in step S4 is carbonized and activated to obtain an activated material. Specifically, the carbonization activation conditions are: heating rate 4 °C / min, temperature 400 °C, treatment time 4 h; protective gas is nitrogen and argon.

[0055] S6, post-treatment: pickling and water washing the activated material obtained in step S5 until it is neutral, and drying to obtain a low-temperature carbonized material rich in microporous structure. Specifically, the pickling solution is hydrochloric acid and formic acid with a mass fraction of 3%.

[0056] S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores. Specifically, the conditions for high temperature carbonization are: heating rate 2 °C / min, carbonization temperature 1300 °C, and carbonization time 5 h.

[0057] Example 5 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with high platform capacity, and its preparation method comprises the following steps: S1. Raw material pretreatment: crush and sieve the biomass raw materials to obtain preliminary raw materials. Specifically, the biomass raw materials are walnut shells, coconut shells, apricot shells, coffee shells, peanut shells, fruit peels, reeds, wood chips, bamboo chips, sunflower stalks, corn stalks, wheat stalks, and starch.

[0058] S2. Alkaline solution treatment: The preliminary raw material obtained in step S1 is treated under alkaline solution conditions to obtain a biomass raw material treated with alkaline solution. Specifically, the alkaline solution is sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution, potassium hydroxide solution, potassium carbonate solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 4 mol / L; the temperature control reaction conditions are: temperature 70°C, time 7h.

[0059] S3, lignin removal treatment: centrifuge the biomass raw material treated with the alkaline solution in step S2, then acid wash and water wash to neutrality, and finally dry to obtain a biomass raw material with some lignin removed. Specifically, the acid washing solution is a hydrochloric acid and nitric acid solution with a mass fraction of 7%.

[0060] S4, activator treatment: the biomass raw material with some lignin removed obtained in step S3 is subjected to temperature-controlled reaction in the activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator. Specifically, the filtered activator filtrate is calibrated and then added to the required concentration, the activator is magnesium citrate and calcium citrate, the amount of activator added is 8 wt.% of the amount of biomass raw material added, and the temperature-controlled reaction conditions are: temperature 70°C, time 7h.

[0061] S5, carbonization activation: the biomass raw material rich in activator obtained in step S4 is carbonized and activated to obtain an activated material. Specifically, the carbonization activation conditions are: heating rate 7 °C / min, temperature 500 °C, treatment time 4 h; protective gas is nitrogen and argon.

[0062] S6, post-treatment: pickling and water washing the activated material obtained in step S5 until it is neutral, and drying to obtain a low-temperature carbonized material rich in microporous structure. Specifically, the pickling solution is hydrochloric acid with a mass fraction of 5%.

[0063] S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores. Specifically, the conditions for high temperature carbonization are: heating rate 2°C / min, carbonization temperature 1400°C, and carbonization time 3 h.

[0064] Application Example 1 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with a high platform capacity. The preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the coconut shell raw material, sieve through 100 meshes to obtain coconut powder raw material.

[0065] S2, alkaline solution treatment: soak the coconut powder sieved in step S1 in a potassium hydroxide solution with a concentration of 2.5 mol / L, heat it in a water bath to 80° C., and keep it for 2 hours.

[0066] S3, lignin removal treatment: the coconut powder treated with alkali in step S2 is centrifuged and dried, and then washed with a 2% hydrochloric acid solution by mass, and then washed with pure water until the coconut powder is neutral, and finally dried at 80° C. for 12 h.

[0067] S4, activator treatment: soak the coconut powder with part of lignin removed obtained in step S3 in a zinc chloride solution with a mass fraction of 8%, in a water bath at 80° C., and maintain for 10 hours; then centrifuge and dry, and dry at 80° C. for 12 hours.

[0068] S5, activated carbonization: the coconut powder dried in step S4 is heated to 500° C. at 5° C. / min under a nitrogen atmosphere and kept warm for 4 h.

[0069] S6, post-processing: The coconut powder carbonized at low temperature in step S5 is washed with a hydrochloric acid solution with a mass fraction of 2%, then washed with water to a pH value of 7, and finally dried.

[0070] S7, high temperature carbonization: the coconut powder dried in step S6 is heated to 1200° C. at 2° C. / min under a nitrogen atmosphere and kept at this temperature for 5 hours to obtain the final hard carbon negative electrode material.

[0071] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 60 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP double-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0072] Application Example 2 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material with a high platform capacity. The preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the reed raw material, sieve through 100 meshes to obtain reed powder raw material.

[0073] S2. Alkaline solution treatment: soak the reed powder sieved in step S1 in a sodium carbonate solution with a concentration of 6 mol / L, heat it in a water bath to 100° C., and keep it for 6 hours.

[0074] S3, lignin removal treatment: after centrifuging and drying the reed powder treated with alkali in step S2, add 2% by mass nitric acid solution for washing, then wash the reed powder with pure water until it is neutral, and finally dry it at 80°C for 12h.

[0075] S4, activator treatment: soak the reed powder with some lignin removed obtained in step S3 in a 5% by mass magnesium citrate solution, in a water bath at 80° C. for 10 h, then centrifuge and dry at 80° C. for 12 h.

[0076] S5, activated carbonization: the reed powder dried in step S4 is heated to 600° C. at 5° C. / min under a nitrogen atmosphere and kept at this temperature for 2 hours.

[0077] S6, post-treatment: the reed powder after low-temperature carbonization in step S5 is washed with a 2% by mass nitric acid solution, then washed with water to a pH value of 7, and finally dried.

[0078] S7. High-temperature carbonization: The reed powder dried in step S6 is heated to 1300° C. at 2° C. / min in a nitrogen atmosphere and kept at this temperature for 3 h to obtain a final hard carbon negative electrode material.

[0079] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 60 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP double-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0080] Comparative Example 1 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material. The preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the coconut shell raw material, sieve through 100 meshes to obtain coconut powder raw material.

[0081] S2, lignin removal treatment: soak the coconut powder sieved in step S1 in a zinc chloride solution with a mass fraction of 8%, in a water bath at 80° C., and maintain for 10 hours.

[0082] S3, activator treatment: centrifuge and dry the coconut powder soaked in the zinc chloride solution in step S2, and then dry it at 80° C. for 12 hours.

[0083] S4, activated carbonization: the coconut powder dried in step S3 is heated to 500° C. at 5° C. / min under a nitrogen atmosphere and kept warm for 4 h.

[0084] S5, post-processing: The coconut powder carbonized at low temperature in step S4 is washed with a hydrochloric acid solution having a mass fraction of 2%, then washed with water to a pH value of 7, and finally dried.

[0085] S6, high temperature carbonization: the coconut powder dried in step S5 is heated to 1200° C. at 2° C. / min under a nitrogen atmosphere and kept at this temperature for 5 hours to obtain the final hard carbon negative electrode material.

[0086] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 60 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP double-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0087] Comparative Example 2 This embodiment relates to a biomass hard carbon sodium ion battery negative electrode material. The preparation method thereof comprises the following steps: S1. Raw material pretreatment: crush the coconut shell raw material, sieve through 100 meshes to obtain coconut powder raw material.

[0088] S2, alkaline solution treatment: soak the coconut powder sieved in step S1 in a potassium hydroxide solution with a concentration of 2.5 mol / L, heat it in a water bath to 80° C., and keep it for 2 hours.

[0089] S3, lignin removal treatment: the coconut powder treated with alkali in step S2 is centrifuged and dried, and then washed with a 2% hydrochloric acid solution by mass, and then washed with pure water until the coconut powder is neutral, and finally dried at 80° C. for 12 h.

[0090] S4, activated carbonization: the coconut powder dried in step S3 is heated to 500° C. at 5° C. / min under a nitrogen atmosphere and kept warm for 4 h.

[0091] S5, post-processing: The coconut powder carbonized at low temperature in step S4 is washed with a hydrochloric acid solution having a mass fraction of 2%, then washed with water to a pH value of 7, and finally dried.

[0092] S6, high temperature carbonization: the coconut powder dried in step S5 is heated to 1200° C. at 2° C. / min under a nitrogen atmosphere and kept at this temperature for 5 hours to obtain the final hard carbon negative electrode material.

[0093] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 60 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP double-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0094] In order to effectively evaluate the technical effect of the present invention, the application examples 1-2 and the comparative examples 1-2 were tested and compared as follows: The constant current charge and discharge test measured that the first week charging specific capacity of the hard carbon electrode in Application Example 1, Application Example 2, Comparative Example 1 and Comparative Example 2 were 328.07, 336.64, 294.44 and 282.07 mAh / g respectively. The constant current test results showed that the hard carbon materials in Application Example 1 and English Example 2 showed higher capacity and first efficiency after the combination of alkali treatment and activator activation, while the hard carbon material in Comparative Example 1 that was only activated but not pre-treated with alkali showed lower capacity; the material in Comparative Example 2 that was only treated with alkali showed lower capacity.

[0095] In addition, the specific surface areas of the hard carbon electrodes in Application Example 1, Application Example 2, Comparative Example 1 and Comparative Example 2 are 7.04, 6.83, 35.31 and 7.72 m 2 / g, and the corresponding first-week efficiencies are 91.40, 93.21, 86.28, and 90.78, respectively. Application Example 1 and Application Example 2 have lower specific surface areas and higher first-week efficiencies after alkali treatment combined with activation by an activator; the material in Comparative Example 1 without prior alkali treatment has higher specific surface areas and lower first-week efficiencies. This shows that the alkali treatment combined with the activation treatment process in the present invention can enable the hard carbon material to simultaneously achieve the inventive effects of high capacity and high first-week efficiency.

[0096] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity, characterized in that The following steps are involved: S1. Raw material pretreatment: crushing and sieving the biomass raw materials to obtain preliminary raw materials; S2, alkaline solution treatment: the preliminary raw material obtained in step S1 is treated under alkaline solution conditions under temperature control to obtain a biomass raw material treated with alkaline solution; S3, lignin removal treatment: centrifuging the biomass raw material treated with the alkaline solution in step S2, then acid-washing and water-washing to neutrality, and finally drying to obtain a biomass raw material with some lignin removed; S4, activator treatment: the biomass raw material from which part of the lignin has been removed obtained in step S3 is subjected to temperature-controlled reaction in an activator solution, followed by centrifugation and drying to obtain a biomass raw material rich in activator; S5, carbonization and activation: carbonizing and activating the biomass raw material rich in activating agent obtained in step S4 to obtain an activated material; S6, post-processing: pickling and washing the activated material obtained in step S5 to neutrality, and drying to obtain a low-temperature carbonized material rich in microporous structure; S7, high temperature carbonization: the carbonized material obtained in step S6 is subjected to high temperature carbonization to obtain a sodium ion battery hard carbon negative electrode material rich in micropores.

2. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S2, the alkaline solution is one or more of sodium hydroxide solution, sodium carbonate solution, sodium bicarbonate solution, potassium hydroxide solution, potassium carbonate solution, barium hydroxide solution, and calcium hydroxide solution, and the concentration of the alkaline solution is 2-10 mol / L; the temperature control reaction conditions are: temperature 60-120°C, time 2-10h.

3. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S4, the activator is one or more of zinc chloride, magnesium chloride, calcium chloride, zinc nitrate, magnesium nitrate, zinc acetate, magnesium acetate, calcium acetate, zinc gluconate, magnesium gluconate, calcium gluconate, zinc citrate, magnesium citrate, and calcium citrate. The amount of the activator added is 5-20 wt.% of the amount of biomass raw material added, and the temperature control reaction conditions are: temperature 50-80°C, time 5-20h.

4. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S5, the carbonization activation conditions are: heating rate 2-10°C / min, temperature 300-600°C, treatment time 2-5 h; protective gas is nitrogen and / or argon.

5. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S7, the high temperature carbonization conditions are: heating rate 0.5-5°C / min, carbonization temperature 1200-1600°C, and carbonization time 2-10 h.

6. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In steps S3 and S6, the pickling solution is one or more of hydrochloric acid, nitric acid solution, hydrofluoric acid, formic acid, acetic acid, and phytic acid with a mass fraction of 2-10%.

7. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S4, the concentration of the filtered activator filtrate is calibrated and then added to reach the required concentration.

8. The method for preparing a negative electrode material of a biomass hard carbon sodium ion battery with a high platform capacity according to claim 1, characterized in that: In step S1, the biomass raw material is one or more of walnut shells, coconut shells, apricot shells, coffee shells, peanut shells, fruit peels, reeds, wood chips, bamboo chips, sunflower stalks, corn stalks, wheat stalks, and starch.

9. A biomass hard carbon sodium ion battery negative electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for extracting cellulose from biomass, method for preparing hard carbon material by using cellulose, battery negative electrode and sodium ion battery

    CN116770611A

  • Cotton straw-based biomass hard carbon negative electrode material and preparation method and application thereof

    CN117865127A

  • Preparation method of porous high-capacity biomass hard carbon negative electrode material of sodium-ion battery

    CN118929634A

  • Manufacturing method of partially crystaline porous active carbon, supercapacitor using the active carbon and manufacturing method of the supercapacitor

    KR1020180130946A

  • Method of obtaining active coal

    RU2391290C1